Radicalising Community Development within Social Work through Popular Education—A Participatory Action Research Project. (8th March 2019) - Westoby, Peter; Lathouras, Athena; Shevellar, Lynda
Abstract: This article reports upon the efforts of three social work/social science academics in partnership with social and community practitioners, at radicalising community development (CD) within social work. The project was motivated by painful political events and processes unfolding around the world in 2017 and led to the design of a participatory action research approach with thirty-three practitioners. Engaging in several cycles of research (pre- and post questionnaires, observation, focus groups and interviews) and action learning (a popular education knowledge exchange day, a community of practice day and prototyping new projects) several new initiatives were implemented, including the formation of a new Popular Education Network. Reflections and discussion consider the implications of radicalising CD within social worker practice through combining education, organising and linking to progressive social movements. The article overall makes the case that popular education could be a crucial element in enabling the radicalisation of CD within social work.